THE STRENGTH OF GOOD CORPORATE GOVERNANCE IN MODERATING THE EFFECTS OF GREEN INTELLECTUAL CAPITAL ON GREEN COMPETITIVE ADVANTAGE AND FIRM PERFORMANCE - Hexana Sri Lastanti; Yvonne Augustine (Jurnal Akuntansi Trisakti, 2022)
This study aims to determine the effects of intellectual capital on green competitive advantage and firm performance with good corporate governance as a moderating variable for this relationship. It uses primary data questionnaires distributed to employees with at least 3 years of working experience. The findings of this study show that green structural capital, green relational capital, and green intellectual capital have positive effects on green competitive advantage. Meanwhile, green human capital and green relational capital have positive effects on firm performance. On the other hand, green human capital has no effects on green competitive advantage. Likewise, green structural capital and green intellectual capital have no effects on firm performance. Good corporate governance heightens the effects of green structural capital, green relational capital, and green intellectual capital on green competitive advantage. Also, it heightens the effects of green human capital, green relational capital, and green intellectual capital on firm performance. Regardless of its positive effects, good corporate governance is unable to moderate the effects of green human capital on green competitive advantage and the effects of green structural capital on firm performance.